2021 Financial Sector Assessment Program Review : Background Paper On Quantitative Analysis. (Policy Papers; Policy Paper ;, 2021)
This paper reviews quantitative tools of financial stability assessments under the Financial Sector Assessment Program (FSAP). A key focus of FSAPs is on methodologies to gauge risks on a system-wide level and propose mitigating measures. Therefore, the paper concentrates on the main elements of the FSAP's macroprudential stress testing framework:(i) the interaction among solvency, liquidity, and contagion risks in the banking sector, (ii) the assessment of the health of nonbank financial institutions (NBFIs), their interactions with banks and their impact on financial markets, (iii) the assessment of the health of nonfinancial sectors and their links to the financial sector, and (iv) macroprudential policy analysis. The paper also reviews recent improvements in microprudential bank solvency stress testing-an important foundation for the macroprudential stress testing framework-and discusses new tools for emerging risks (climate change, fintech, and cyber).